ChemInform Abstract: A General Route to Fluorinated 3, 3‐Disubstituted 2‐Oxindoles via a Photoinduced Radical Cyclization of N‐Arylacrylamides under Catalyst‐Free Conditions. Issue 35 (August 2016) - An, Yuanyuan; Li, Yuewen; Wu, Jie
Abstract: A catalyst‐free radical cyclization of N‐arylacrylamides with fluorinated alkyl iodides under ultraviolet radiation is presented for the first time.